ANALISIS PENGARUH KUALITAS PRODUK, PROMOSI, KEPERCAYAAN MEREK, DAN KEPUASAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA VARIO (Studi pada pengguna Motor Honda Vario di Kecamatan Muara Bulian) - Siti Marlina AZ (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The purpose of this study was to analyze the influence of the quality of the products, promotions, brand trust and satisfaction of consumers against purchasing decisions (case study of user Honda Vario Muara Bulian district). The number of samples in the study was 80 respondents and convience method using sampling. This research method using multiple linear regression test analysis. The results of this study showed that the quality of the products, promotions, brand and trust our satisfaction of influential consumers significantly to purchasing decisions. Test the quality of the data used in this study using the test validity and reliability as for testing the validity, reliability, while for hypothesis testing in this study using a coefficient determination test, test and test F T. multiple linear regression test results it can be concluded that there is a significant influence of the variable quality of products, promotions, brand, trust and satisfaction of consumers against purchasing decisions.Keyword: product quality, promotion, brand Trust, satisfaction of consumers and purchasing decisions.